PENERAPAN STRATEGI PJBL BERBANTUAN MODUL 6M MENINGKATKAN PERILAKU SISWA DALAM PENGELOLAAN SAMPAH - Fitri Rahmawati (Jurnal Ilmiah Mandala Education (JIME), 2017)
The purpose of this study was to determine the increase in Knowledge, Attitudes, and Behavior Based Waste management students to 6M in SMP 26 Malang Go To School Program Adiwiyata.This research  includes Classroom Action Research (CAR), carried out using two cycles. Subject consist of student class seven A, B, C, and D totaling 157 student. Improved Attitude first cycle students at 80,1 mean pretest, posttest 86,3, and increased 6,2% with a 0,3 Gain Score classified as moderate. Second cycle  of 80,1 pretest, posttest increased 89,7 and (9,6%) with a 0,5 Gain Score. In first cycle students at 58,4 mean pretest, posttest 65,9, and increased 7,5%, 0,2 Gain Score is low. Second cycle average of 63,7 pretest, posttest 77,4, and increased by 13,7% with 0,4 Gain Score is classified